2014
DOI: 10.1007/s40256-013-0060-1
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Reduction with Ivabradine in Patients with Acute Decompensated Systolic Heart Failure

Abstract: In the present cohort of patients with ADSHF and HR >70 bpm, the selective reduction of HR with oral ivabradine was safe and efficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 27 publications
3
25
0
4
Order By: Relevance
“…They noted a significant reduction in HR after the introduction of oral ivabradine, correlated with the reduction of NT-proBNP values and NYHA class. These results suggested that the addition of oral ivabradine before in that population-might be safe and efficient [18].…”
Section: Acute Decompensated Systolic Heart Failurementioning
confidence: 78%
“…They noted a significant reduction in HR after the introduction of oral ivabradine, correlated with the reduction of NT-proBNP values and NYHA class. These results suggested that the addition of oral ivabradine before in that population-might be safe and efficient [18].…”
Section: Acute Decompensated Systolic Heart Failurementioning
confidence: 78%
“…Sargento et al [5 ]shared their experience in 10 consecutive patients with acute HF and severely depressed LVEF who were administered ivabradine for HR control, also proving it to be effective and safe. The largest experience reported in the literature focuses on controlling catecholamine-induced tachycardia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, beta-blockers should not be initiated until patient stabilization in any patients who present with congestive signs and symptoms [3], so ivabradine may be useful in these situations. Ivabradine is a safe and well-tolerated drug in acute HF [4,5,6], so it seems to be an attractive option to avoid excessive tachycardization.…”
Section: Introductionmentioning
confidence: 99%
“…In SHIFT, the drug was not studied in patients with acute decompensated heart failure and thus is not indicated for such patients, through recent data [17,18] suggest that beginning the drug early during a hospitalization for acute decompensated heart failure is acceptably safe and is effective in lowering heart rate. The drug also is contraindicated in patients with blood pressure less than 90/50 mmHg, and in the presence of sick sinus syndrome, sinoatrial block, or third degree AV block, unless a functioning demand pacemaker is present, and in patients with severe hepatic impairment or concomitant use of strong cytochrome P450 3A4 (CYP3A4) inhibitors or enhancers (ivabradine is metabolized in the liver by the P450 CYP 3A4 system).…”
Section: Ivabradinementioning
confidence: 99%